2009
DOI: 10.1021/es902033j
|View full text |Cite
|
Sign up to set email alerts
|

Silica−Volatile Interaction and the Geological Cause of the Xuan Wei Lung Cancer Epidemic

Abstract: Parts of Xuan Wei County, Yunnan Province, China have the highest known lung cancer mortality in nonsmoking women. This high mortality displays a clear spatial relationship to the mines producing coal from the uppermost Permian. Geochemical, petrographic, and grainsize analyses were undertaken on a set of coal samples from Xuan Wei. Results demonstrate that the single geochemical property that makes this coal unusual is its high concentration of quartz (13.5 wt %) of which 35-55% occurs as <10 microm grains. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 26 publications
1
45
0
Order By: Relevance
“…The findings of Barone-Adesi et al (2012) suggest that the 25-fold difference in lung cancer risks found in the previous study (depending on the mine), also in Xuanwei, might be due to use of anthracite versus bituminous coals. Large et al (2009) find that smoky coals from Xuanwei have high quartz content, and suggest that the lethality of such coals might be due to interactions between PM 10 silica particles and organics.…”
Section: Overview Of Health Effectsmentioning
confidence: 80%
“…The findings of Barone-Adesi et al (2012) suggest that the 25-fold difference in lung cancer risks found in the previous study (depending on the mine), also in Xuanwei, might be due to use of anthracite versus bituminous coals. Large et al (2009) find that smoky coals from Xuanwei have high quartz content, and suggest that the lethality of such coals might be due to interactions between PM 10 silica particles and organics.…”
Section: Overview Of Health Effectsmentioning
confidence: 80%
“…Examples indicating such activity include: the frequent occurrence of tonsteins derived from volcanic ashes in many Late Permian coals of southwestern China (Burger et al, 1990Zhou et al, 2000;Dai et al, 2011); the input of syngeneic submarine exhalation to the peat mire (Dai et al, , 2015b; and the high percentages of quartz and chamosite in the Late Permian coals of eastern Yunnan, which are considered to be derived from plume mantlerelated hydrothermal fluids during peat accumulation or at an early stage of diagenesis (Dai and Chou, 2007;Wang et al, 2012). The quartz of syngenetic hydrothermal origin in eastern Yunnan is usually fine to ultra-fine grained, ranging in size from nanometers to less than 20 μm, and may be related to high lung cancer rates in some of the townships in Xuanwei County of eastern Yunnan Large et al, 2009). …”
Section: Control Of Elip On Coal-hosted Ore Depositsmentioning
confidence: 99%
“…Most notable has been the finding that smoky coal users are exposed to high levels of polycyclic aromatic hydrocarbons (PAHs), including the known carcinogen benzo[a]pyrene (BaP) 59 . However, more recently, exposure to crystalline silica (quartz) has gained increasing attention as a potential contributor 1015 . This attention is largely derived from several small studies which have identified higher amounts of quartz in samples of smoky than smokeless coal and a positive correlation between quartz content of smoky coal and lung cancer rates in the area.…”
Section: Introductionmentioning
confidence: 99%